Gastrointestinal Pathogen Colonization and the Microbiome in Asymptomatic Kidney Transplant Recipients - Westblade, Lars F. (Transpl Infect Dis, 2019)
BACKGROUND. In kidney transplant recipients, gastrointestinal (GI) pathogens in feces are only evaluated during diarrheal episodes. Little is known about the prevalence of GI pathogens in asymptomatic individuals in this population. METHODS. We recruited 142 kidney transplant recipients who provided a non-diarrheal fecal sample within the first 10 days after transplantation. The specimens were evaluated for GI pathogens using the BioFire® FilmArray® GI Panel (BioFire® Diagnostics, LLC; Salt Lake City, UT), which tests for 22 pathogens. The fecal microbiome was also characterized using 16S rRNA gene sequencing of the V4-V5 hypervariable region. We evaluated whether detection of Clostridioides difficile and other GI pathogens was associated with post-transplant diarrhea within the first 3 months after transplantation. RESULTS. Among the 142 subjects, a potential pathogen was detected in 43 (30%) using the GI Panel. The most common organisms detected were C. difficile (n=24, 17%), enteropathogenic Escherichia coli (n=8, 6%), and norovirus (n=5, 4%). Detection of a pathogen on the GI panel or detection of C. difficile alone was not associated with future post-transplant diarrhea (P > 0.05). The estimated number of gut bacterial species was significantly lower in subjects colonized with C. difficile than those not colonized with a GI pathogen (P = 0.01) CONCLUSION. Colonization with GI pathogens, particularly C. difficile, is common at the time of kidney transplantation but does not predict subsequent diarrhea. Detection of C. difficile carriage was associated with decreased microbial diversity and may be a biomarker of gut dysbiosis.